(untitled) - Hanneman, Robert A. (San Francisco, CA, 2013)
Basic Statistics for Social Research teaches core general statistical concepts and methods that all social science majors must master to understand (and do) social research. Its use of mathematics and theory are deliberately limited, as the authors focus on the use of concepts and tools of statistics in the analysis of social science data, rather than on the mathematical and computational aspects.Each chapter contains instructive features to aid students in understanding and mastering the various statistical approaches presented in the book, including: Learning objectives; Check quizzes after many sections and an answer key at the end of the chapter;Summary; Key terms;End-of-chapter exercises;SPSS exercises (in select chapters)
Keywords: Social sciences,Khoa học xã hội; Statistical methods,Phương pháp thống kê